Negative perception in those at highest risk - potential challenges in colorectal cancer screening in an urban Asian population - Hilmi, I.; Hartono, J.L.; Goh, K.L. (Asian Pacific Organization Cancer Prevention, 2010)
Introduction: Colorectal carcinoma (CRC) is the second commonest malignancy in Malaysia, with the highest incidence seen in the Chinese. The aim of this study is to examine the knowledge of CRC and to identify potential barriers for screening, which has yet to be carried out on a nationwide scale. Methods: Subjects were recruited consecutively from friends and relatives accompanying patients to the general medical clinic in a tertiary hospital in Kuala Lumpur. Interviews were carried out using a standardized questionnaire for the Asia Pacific CRC working group based on the Health Belief Model (HBM). Results: 991 subjects were interviewed. From our study, 414 (41.8%), 500 (50.5%) and 646 (65.2%) could not identify any of the symptoms, risk factors and screening methods for CRC respectively. Only 384 (38.7%) were agreeable to undergo screening. Independent factors associated with willingness to undergo screening were as follows; Malay and Indian race compared to the Chinese [aOR 2.73 (1.87, 3.98) and 3.04 (2.02, 4.59) respectively], perceived susceptibility, perceived barriers to screening, doctor's recommendation and personal contact with CRC. Conclusions: Knowledge of CRC and CRC screening is low among the Malaysian population. The majority are not willing to undergo screening, the Chinese paradoxically being the least willing despite being at greatest risk.